Pertarungan Antara Ekonomi-Politik Dalam Gelanggang Kepentingan Hak Milik Pribadi - Darto Simamora (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Nemo Dat Quod Non Habet (no one can give what he does not have). This expression is even more meaningful when humans realize that they are not alone on this earth. In reality, humans live together with others. In this togetherness, humans must always respect and maintain human rights as a legacy of the Creator. This inheritance is a free grace from God so that humans can live well according to God's law. One of those inheritances is private property rights. Private property rights are authentic rights in every human being. Every human being has the right to private property in the form of material goods and psychological ones. It means that man by nature already has it in him. Humans do not give these rights so they have no right to revoke them. Even if humans do not recognize private property rights. It doesn't mean that the right doesn't exist. In the course of human history, private property rights seem to be lost because of efforts to shrink them with various arguments that support the interests of one party. In reality. It brings suffering to those who are unskilled and have no capital. In addition, there are also radical groups who try to abolish private property rights because they are seen as the root of suffering. In the midst of this uncertain situation, the Christian community does not turn a blind eye to the experiences of the people. The Church promotes a view that is based on the will of God and in accordance with the will of mankind in general, which seeks to establish justice through the commentary on private property rights contained in the Encyclical Centesimus Annus. Private property must be nurtured through work, which is a powerful means of maintaining private property. Humans will take some of the treasures of this earth to be their personal property. Even if a man works for others, he will receive a decent wage to live well. Private property will help humans to develop as the image of God, strengthen human dignity and allow for wider participation of workers in personal development and cultivate this earth. Therefore, humans must use this natural wealth with human knowledge. From this function, it is clear that private property has individual and social dimensions. Private property must be protected from all efforts to shrink it. In this case, the state (government) and religious communities have the duty as the main line to protect it. This study uses library research methods (library research). The author uses the CA Encyclical as the main source. Meanwhile, in its presentation, the writer uses descriptive-critical method.